Hubungan Pemberian Susu Formula dengan Kejadian Diare pada Bayi Usia 0-6 Bulan - Iskandar, Iskandar; Maulidar, Maulidar (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2016)
There are many factors effects on giving formulation milk, such as income, behavior pattern, the baby find not colostrum and ASI exclusive, behaviour giving of formulation milk, MP ASI, safety and healthy equipment, contamination microbe. The aim of this research is to known the factors that effect on giving formulation milk about diarhea for baby at Teupin Raya Public healt centre regency Pidie.Research Method: This method is analitical descriptive by using design based on study case control that already done on 08th-23rd of february 2014 by samples 72. The research was quota simple samples that’s consists of 36 samples as case and 36 samples control. Variables are the effect of giving formulation milk about diarhea. Data was collected by interview that using questionare, then analyzed it by proving based on chi square test in stage of accurancy (0,05) and Odd Ratio.Result of research: This research show that thereis influance the way of given powder milk to baby with diarhea that ages 0-6 bulan month with value P ; 0,009 (p < 0,05) and the result analysis got by score OR:4,09 ( CI : 1,52 – 11,00). Conclution and suggestion : The baby that given formulation milk it does not give protection effect while diarhea happening than the baby that given powder milk to baby. The writen expected to medical employed at Publik Healt Centre to know the influences of the way of given formulation milk to baby with diarhea